2014
DOI: 10.1088/1748-0221/9/10/c10041
|View full text |Cite
|
Sign up to set email alerts
|

Toward a RPC-based muon tomography system for cargo containers.

Abstract: A large area scanner for cosmic muon tomography is currently being developed at University of Bristol.Thanks to their abundance and penetrating power, cosmic muons have been suggested as ideal candidates to scan large containers in search of special nuclear materials, which are characterized by high-Z and high density. The feasibility of such a scanner heavily depends on the detectors used to track the muons: for a typical container, the minimum required sensitive area is of the order of 100 2. The spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Using fewer muons provides significant time savings but lower quality images, while a higher number of measured muons results in improved image contrast and resolution but increased measurement time. Existing studies on muon-CT detectors have demonstrated that muons on the order of millions (requiring minutes to days of measurement time, depending on the size and orientation of the detectors) are required for imaging large scale objects such as cargo containers [4,5,11] or dry casks [21][22][23]. Recent work based on simulations showed that several days (>10 6 muons) are needed to identify the location of spent nuclear fuel in dry casks [21][22][23].…”
Section: Cosmic Ray Muon Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Using fewer muons provides significant time savings but lower quality images, while a higher number of measured muons results in improved image contrast and resolution but increased measurement time. Existing studies on muon-CT detectors have demonstrated that muons on the order of millions (requiring minutes to days of measurement time, depending on the size and orientation of the detectors) are required for imaging large scale objects such as cargo containers [4,5,11] or dry casks [21][22][23]. Recent work based on simulations showed that several days (>10 6 muons) are needed to identify the location of spent nuclear fuel in dry casks [21][22][23].…”
Section: Cosmic Ray Muon Tomographymentioning
confidence: 99%
“…Recently, the use of muons in nuclear nonproliferation and safeguards verification applications has received attention as a passive and penetrating way to interrogate objects. This endeavor has been assisted by the development of detectors that can measure and provide information related to the incoming and outgoing trajectories of individual muons [2][3][4][5][6]. Recently, cosmic ray muons have been investigated for volcano imaging [7][8][9] and cargo scanning applications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Cosmic ray muon imaging has found many applications, some that can sacrifice high resolution imaging for short acquisition and object detection times [3,5], and some that require high resolution images with less emphasis on the acquisition time [17,18]. An example of early detection of a lead sample is given in Figure 20 for 100, 1000, 5000 and 25000 muons.…”
Section: Image Recording Time and Tracker Improvementsmentioning
confidence: 99%
“…For that purpose, a small-scale prototype consisting of 12 RPCs with a fiducial region of 48 x 48 cm 2 was developed, and after the successful completion of this system, a large-scale prototype consisting of 24 RPCs with a fiducial region of 178 x 54 cm 2 was built. Details and results of both systems can be found in [4,5]. The simulated detectors used in this study have been based on these detectors; in particular, the intrinsic spatial resolution was assumed to be 450 µm based on the prototype results.…”
Section: Introductionmentioning
confidence: 99%